PENGARUH DISIPLIN KERJA, KOMUNIKASI, KEPEMIMPINAN DAN MUTASI TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) DI LINGKUNGAN SEKRETARIAT DAERAH PEMERINTAH KOTA TANJUNGBALAI - Suardi Suardi (Universitas Dharmawangsa, 2018)
Efforts to improve the performance of the State Civil Servant (ASN) as a servant of the State andpublic servants, the government seeks to further optimize the function of the State Civil Apparatus(ASN). This is done, among others, by improving the personnel system, empowering and improvingthe accountability of the State Civil Apparatus (ASN) itself. The low quality of service provided bythe State Civil Apparatus (ASN) to the community which is one of the benchmarks to assess theperformance of the State Civil Apparatus (ASN) could be caused by many things. When thegovernment is unable to act decisively against the Civil State Official (ASN) rules and not disciplinein performing duties as servant of State and public servant, then selamnyalah performance of StateCivil Apparatus (ASN) will be dilapidated and far from what expected. However it is necessary toconsider the communication within the State Civil Servant (ASN). The result of this researchconcludes that there is influence of work discipline, leadership, communication and mutation toperformance of State Civil Apparatus (ASN) in Local Secretariat Environment of TanjungbalaiGovernment partially or simultaneously. And the ability of work discipline, leadership,communication and mutation in explaining the performance of State Civil Apparatus (ASN) is equalto 60.9% the remaining 39.1% is explained by other variables not included in this research model